“Financial Stability”: A Nightmare for Retired Healthcare Professionals in Southwestern Nigeria: An Interpretative Phenomenology - Aderonke Julienne Adetunji MSc, BNSc, RPHN, RNE, RM, RN; Emelda Zandile Gumede PhD, Mcur, RNE, RM, RN (SAGE Open Nursing)
Introduction The transition from work to retirement has been an issue of lively scientific discussion for many and is driven by the constant fear of what is going to happen to their financial stability because of a history of delayed pension payments. Budgetary constraints by the Federal Government led to delays in paying pension benefits. Pension Commission (PenCom) works to ensure adequate budgetary provisions and timely release of funds to reduce the backlog in payments. Many retirees lack proper retirement and financial planning while PenCom continues to emphasize the importance of planning for retirement to ensure financial security. Objective This study was conducted to explore the financial stability of healthcare professionals postretirement, in Nigeria. Methods An Interpretative Phenomenological Analysis (IPA) design was utilized. The study population consisted of retirees who were 2 years old or older from three tertiary institutions in purposively selected states in Southwestern Nigeria. After obtaining consent, an in-depth interview and focused group discussion (FGD) were used to collect data. Both interviews and FGD were audio recorded, transcribed verbatim, and analysis followed, IPA steps by Smith et al. This was there after being imported into NVivo version 12. Results Respondents thought they were financially prepared for retirement, however, the delay of 6 to 15 months before the pension payout was unforeseen. Retirees opted for alternative means of income, like petty trading, Tuck shops, molding blocks, livestock-rearing goats, and working in private institutions. An emerging theme of “Financial instability” and three subthemes: alternate income; flexi-work and exploring hidden talents. Financial security is the key to a peaceful retirement. Conclusion Employees need to be prepared for retirement by having multiple sources of funding to enjoy a peaceful retirement